2011
DOI: 10.1093/brain/awr204
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric MRI analysis improves detection of focal cortical dysplasia type II

Abstract: Focal cortical dysplasias type II (FCD II) are highly epileptogenic lesions frequently causing pharmacoresistant epilepsy. Detection of these lesions on MRI is still challenging as FCDs may be very subtle in appearance and might escape conventional visual analysis. Morphometric MRI analysis is a voxel-based post-processing method based on algorithms of the statistical parametric mapping software (SPM5). It creates three dimensional feature maps highlighting brain areas with blurred grey-white matter junction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
169
3
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(200 citation statements)
references
References 41 publications
22
169
3
4
Order By: Relevance
“…FCD has been demonstrated as the most common pathology underlying MR-epilepsies, 48 and among common imaging characteristics of FCD, gray-white matter junction blurring occurs most frequently. 33,49 Consistent with the published literature, 30,32 we found the gray-white junction file to be the most helpful feature map. Others have reported that the extension file by itself can also uniquely identify some subtle lesions, 32 but our analysis of this cohort did not support this observation.…”
Section: Sensitivity Of Mapsupporting
confidence: 86%
See 1 more Smart Citation
“…FCD has been demonstrated as the most common pathology underlying MR-epilepsies, 48 and among common imaging characteristics of FCD, gray-white matter junction blurring occurs most frequently. 33,49 Consistent with the published literature, 30,32 we found the gray-white junction file to be the most helpful feature map. Others have reported that the extension file by itself can also uniquely identify some subtle lesions, 32 but our analysis of this cohort did not support this observation.…”
Section: Sensitivity Of Mapsupporting
confidence: 86%
“…[23][24][25][26][27][28][29] Among them, a voxel-based MRI morphometric analysis program (MAP), implemented using parametric mapping software (SPM), has been used to detect subtle cortical malformations with a high degree of sensitivity. [30][31][32] In practice, MAP directs the reader's attention to suspicious brain regions, on the basis of abnormal gray-white junction blurring, abnormal cortical gyration, or abnormal cortical thickness. These features, particularly the blurred gray-white matter junction, are common accompaniments of FCD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, positive MR imaging findings (59% of our patients) were based on conventional visual analysis. Voxel-based postprocessing methods proved a significant benefit in comparison with visual analysis alone 33,34 and would possibly decrease our rate of negative MR imaging findings. However, these techniques apply algorithms not applicable in routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for the automated detection of areas of FCDs on imaging using automated segmentation and postacquisition image-processing algorithms aimed at detecting cortical thickness or gray matter-white matter junction blurring are being developed and, in some situations, are superior to expert human visual analysis. 27 The influence of the 3-T versus the 1.5-T scanner on the detection of the lesion or the resection to lesion volume ratios were not specifically analyzed in our study. However, other studies have shown that the use of 3-T MRI in patients suspected of having a Type 2 FCD improves the detection rate and the lesion characterization because of the transmantle sign being more clearly visible at 3 T. 17 Other novel techniques include the use of optical coherence tomography and the use of high-frequency ultrasonography for micrometer-level intraoperative resolution and the delineation of these lesions.…”
Section: Volumetrics and Epileptogenesismentioning
confidence: 99%